C5 Two cases of acute encephalitis with neurological complications as a seroconversion illness in primary HIV infection (PHI). (23rd May 2012) - Jain, L; Lowe, S; Crowe, G
Abstract : Background: Neurological complications as the presenting feature of PHI are rare and reported in <10% of cases. We describe two cases of sero-conversion illness with rapidly progressive neurological involvement. Case 1: A 43-year-old man presented with diarrhoea, vomiting and rash. On examination he had widespread lymphadenopathy, mouth ulcers and tender hepatomegaly. HIV test was positive (avidity index 50%). 2 weeks later he was readmitted with headache and vomiting. On examination he had left sided weakness and left facial droop. CT head was normal. Cerebro-spinal fluid (CSF) showed an elevated protein 2.99 g/l, WC 48, with and numerous polymorphs visualised. Antibiotics for meningitis were commenced. Serial MRI scans were normal. CD4 count was 640 cell/mm and HIV viral load was 197 000. Antiretrovirals (ARV) were commenced at day 14 and symptoms improved within the next 4 days. 2 months later all weakness and headaches have resolved. Case 2: A 47-year-old British man presented with a collapse following 2 days of personality change and confusion and 10 days of fever, headaches, diarrhoea, myalgia, photophobia and rash. On admission he was confused, pyrexial with a Glasgow Coma Score of 13. He had a normal CT head, CSF protein was 1.5 g/l, RC <5, WC<5, with no organisms seen. Subsequent CSF viral PCR was negative. MRI brain was also normal. No evidence of sepsis was identified. An HIV test on admission was positive (avidity index 65%). HIV test 3 months earlier had been negative. CD4 count was 594 (16%) cells/mm 3 and viral load 462 756 copies/ml. ARVs were commenced on day 7, symptoms improved markedly over the following week. Four weeks post discharge confusion had completely resolved but he reported ongoing mild coordination difficulties. Discussion: Neurological complications of seroconversion are rare but do occur. Early recognition is important through prompt HIV testing and the introduction of ARVs may reduce the incidence of neurological sequelae markedly.